Differential Scanning Calorimetric Analysis of Virgin Coconut Oil, Palm Olein, and their Adulterated Blends - Marikkar, J. M. N.; Kamil, Nisa; Raihana, A. R. (International Coconut Community Journal, 2019)
Virgin coconut oil (VCO) is a premium product with a high market value. Its authenticity and quality assurance are important to safeguard consumers from fraudulent practices. The aim of this study was to investigate the effect of adulteration by palm olein (PO) on differential scanning calorimetric (DSC) heating and cooling profiles of VCO. Pure samples of VCO, PO and their adulterated blends (5 to 30%, w/w) were subjected to thermal analysis by DSC according to a specified temperature program. DSC thermal analysis system software and SAS statistical system were used subsequently to analyze thermal data. Both cooling and heating curves of VCO were found to be vivid for fingerprint comparison of qualitative identification at 5% level of adulteration.